Land Use and Land Cover Dynamics and Properties of Soils under Different Land Uses in the Tejibara Watershed, Ethiopia - Sabiela Fekad Fentie; Kehali Jembere; Endalkachew Fekadu; Dessale Wasie (The Scientific World Journal)
Land use changes have long been considered among many factors responsible for physical and chemical soil degradation. This study was conducted to evaluate land use and land cover (LULC) changes and their cumulative effects over 30 years (from 1989 to 2019) on the current physical and chemical properties of soils in the Tejibara watershed, Ethiopia. Image analysis and LULC classifications were performed using ERDAS IMAGINE 2014 and ArcGIS 10.4 software, respectively. For the determination of soil properties, four land use types (natural forest, eucalyptus plantation, cultivated, and grazing lands) and two soil depths (0–20 and 20–40 cm) were used. Triplicate composite soil samples were collected from each land use type and soil depths. For the determination of physical (texture and bulk density) and chemical soil properties such as electrical conductivity (EC), organic matter (OM), total nitrogen (TN), and available phosphorus (AP), standard laboratory procedures were employed. The image analysis results for all of the years studied show that cultivated lands have increased in area at the expense of forest and grazing lands. Silt content, clay content, AP, and pH were significantly affected by land use as the main effect while the interaction effects of soil depth and land use were significant for total N and OM only. The highest (10.1 mg/kg) and the lowest (4.9 mg/kg) AP contents were observed in the forest and the grazing lands, respectively. Soil total N content was highest in the forest lands (0.32%) and lowest in cultivated lands (0.06%). Concerning OM content, the highest (11.0%) and the lowest (0.8%) values were recorded in the forest and cultivated lands, respectively. Generally, this study showed that land use changes have reduced the areal coverage by forest and grazing lands and have negatively affected the soil properties. This implies that land use change without soil fertility measures that are appropriate to the area could cause enhanced land degradation and thereby reduce the productivity of the study area soils.